Experimental and Computational Study on Effect of Vanes on Heat Transfer and Flow Structure of Swirling Impinging Jet - S. M. Illyas; A. MuthuManokar; A. E. Kabeel (Journal of Applied Fluid Mechanics, 2022)
The study focuses on heat transfer performance and flow structure associated with swirling jet on a flat target surface. The analysis is carried out with helicoid inserts of swirl number S = 1.3 by varying the number of vanes with Reynolds number between 11200 and 35600. The comparison of swirling jet with circular jet is carried out on its heat transfer performance. The heat transfer and flow structure are visualized using thermo-chromic liquid crystal sheet and oil film technique respectively. The numerical simulation is also performed at Re = 24700 for H/D distance between 1 and 4 using computational fluid dynamics. The heat transfer results reveal that the presence of axial recirculation zone at Re = 29800 and 35600 for the triple helicoid affects the uniformity of heat transfer distribution at 0 < X/D < 1.5 at H/D = 3. The axial component of velocity with respect to swirling jet is less than zero in the stagnation area and it increases at 0.57 < r/D < 0.97 for single vane and 0.63 < r/D < 0.97 for double and triple vanes. While the steep increase in tangential velocity of the triple vane jet is apparent at 0 < r/D < 0.5 at H/D = 2 and 3, the maximum value of point radially shifts inward towards the jet. The location of maximum turbulent kinetic energy approaching the surface at about r/D = 0.9 - 1.2 which characterizes the swirling jet at H/D = 2.